Effect of green tea on iron status and oxidative stress in iron-loaded rats - S. Ounjaijean (2018)
Plasma non-transferrin bound iron (NTBI) is potentially toxic and contributes to the generation of reactive oxygen species (ROS), consequently leading to tissue damage and organ dysfunction. Iron chelators and antioxidants are used for treatment of thalassemia patients. Green tea (GT) contains catechins derivatives that have many biological activities. The purpose of this study was to investigate the iron-chelating and free-radical scavenging capacities of green tea extract in vivo. Rats were injected ip with ferric citrate together with orally administered GT extract (GTE) for 4 months. Blood was collected monthly for measurement of iron overload and oxidative stress indicators. Plasma iron (PI) and total iron-binding capacity (TIBC) were quantified using bathophenanthroline method. Plasma NTBI was assayed with NTA chelation/HPLC. Plasma malonyldialdebyde (MDA) was determined by using the TBARS method. Erythrocyte oxidative stress was assessed using flow cytometry. Levels of PI, TIBC, NTBI and MDA, and erythrocyte ROS increased in the iron-loaded rats. Intervention with GT extract markedly decreased the PI and TIBC concentrations. It also lowered the transferrin saturation and effectively inhibited formation of NTBI. It also decreased the levels of erythrocyte ROS in week 4, 12 and 16. Therefore, green tea extract can decrease iron in plasma as well as eliminate lipid peroxidation in plasma, and destroy formation of erythrocyte ROS in the rats challenged with iron. The bifunctional effects could be beneficial in alleviating the iron and oxidative stress toxicity. In prospective, these GTE activities should be further examined in thalassemic animals or humans. © 2008 Bentham Science Publishers Ltd.